Bilateral Vestibulopathy - Current Knowledge and Future Directions to Improve its Diagnosis and Treatment - Bryan K. Ward (Frontiers Research Topics, 2018)
Many patients with bilateral vestibulopathy experience chronic oscillopsia due to failure of the vestibulo-ocular reflex and gait instability due to failure of vestibulo-spinal reflexes. There are numerous potential contributing factors, however, many cases remain idiopathic. The diagnosis of bilateral vestibulopathy is often delayed, placing patients at risk for unnecessary diagnostic tests and late initiation of treatment. Novel diagnostic tests offer new opportunities to characterize patterns of vestibular impairment. With the advent of new therapies, there is urgency to define and better understand patients with bilateral vestibulopathy. This collection includes topics such as an exploration of the large class of patients with bilateral vestibulopathy currently considered idiopathic, by identifying novel pathophysiologic mechanisms. Other topics include a historical perspective on early recognition, the impact of bilateral vestibular impairment on quality of life, and how advances in diagnostics are refining our understanding of what it means to have bilateral vestibulopathy. New developments in treatment strategies for patients with bilateral vestibulopathy are also featured.